THE EFFECT OF DIFFERENT STEAMING TEMPERATURE ON THE PROXIMATE COMPOSITION OF SNAKE FISH (Channa micropeltes) BORTH - M. Alhadid M. Alhadid; Mery Sukmiwati; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study was aimed to determinethe effect of different steaming temperature on the proximate composition of snake head fish (Channa micropeltes) borth. The method used was an experimental method using a completely randomized design (CRD) with 3 treatmentsi.e.ET70 (700C), ET80 (800C) and ET90 (900C). The study results concluded that snakehead fish (C. micropeltes) had a proportion of flesh (52.16%), head (30.71%), scales (5.35%), fins (6.41%) and stomach contents (4.28%).The flesh of snakehead fish (C. micropeltes) hadproximate compositioni.e, 78.25% moisture content, 1.23% ash content, 0.44% fat content, 19.85% protein content, 0.23% carbohydrate content. The steaming temperature significantly affected to the proximate composition and the yield of liquid extract of snakehead fish (C.micropeltes).The average yield of snakehead fish liquid extract was ET70 (80.73%), ET80 (88.79%) and ET90 (90.99%). The best yield was obtained in the ET90 treatment (90.99%). The best proximate composition of snakehead fish liquid extract (C.micropeltes)wasmoisture content of ET70 (70.76%), protein content of ET70 (27.01%), fat content of ET70 (0.62%), ash content of ET90(1.54%), carbohydrate of ET90 (0.73%). Keywords:Broth, Channa micropeltes.,Steaming, Temperature